Exploratory Study of Romanian Generation Z Perceptions of Green Restaurants - Daniel I. Chiciudean; Vanessa P. Shonkwiler; Iulia C. Mureșan; Alina Zaharia; Gabriela O. Chiciudean (Administrative Sciences, 2024)
The hospitality industry has taken advantage of consumers’ increasing concerns regarding environmental issues. Worldwide, green restaurants have increased their profitability by using environmental attributes as a competitive advantage. In Romania, restaurants could profit from this new trend. This study aims to determine the perception of Generation Z consumers regarding green restaurants, since these younger consumers seem to have adopted more eco-friendly behavior compared to previous generations. Another objective of the study refers to assessing the importance of attributes relating to environmental protection and organic food when choosing a restaurant, consequently revealing a suitable market segment for this type of restaurant. In order to determine their degree of knowledge related to the concept of green restaurant, potential consuming behavior if implemented, and identifying the factors considered important when choosing a restaurant, this research compiles information from individuals belonging to Generation Z. Using principal component analysis, five factors were obtained, among which the “health and fresh food” was the most important. Based on the five dimensions, K-means cluster analysis led to three profiles of consumers. “Pro-environmental and convenience seekers” represent the largest cluster and should be considered the main target for future green restaurant practitioners. Additionally, our study finds an overall positive attitude toward green restaurants among the respondents and, more specifically, opinions on how these restaurants could address environmental issues and offer organic food, both important factors for Generation Z. This translates into a strong incentive for future entrepreneurs considering this business model in Romania.